How To Write Better Copy - Steve Harrison
Whether you're a writer in need of inspiration, a one-woman-band drumming up work from new clients, or simply want to persuade your colleagues to adopt your view, this book will help you write better copy. It starts with thinking before writing, and the all-important Brief, then takes you step-by-step from writing a headline to getting the response you want from readers.